Effect of optimizing the nursing process of green channel on time course of intravenous thrombolysis for acute ischemic stroke (优化绿色通道护理流程对急诊缺血性脑卒中静脉溶栓时间节点的影响) - PENG Hong (彭红); LIU Ruihua (刘瑞华); LI Xue (李雪); ZHAN Qian (张倩) (中西医结合护理)
Objective To investigate the effect of optimizing the nursing process of green channel on time course of intravenous thrombolysis for acute ischemic stroke (AIS). Methods Totally 99 AIS patients who received intravenous thrombolysis were divided into two groups according to the according to date of hospital admission: 41 cases who received intravenous thrombolysis before implementation of optimized nursing process of green channel (between November 2020 and March 2021) were included as the control group, 48 cases who received intravenous thrombolysis after implementation of optimized nursing process of green channel (between April 2021 and October 2021) were included as the observation group. The time between admission to CT scanning, time between admission to signing the informed consent, door-to-needle time (DNT) and proportion of patients with DNT≤35 min were measured and compared between groups. Results Shorter time between admission to CT scanning, time between admission to signing the informed consent and door-to-needle time were reported in the observation group than those in the control group(P＜0. 0). There were more patients with DNT≤35 min in the observation group than those in the control group(89. 58% vs. 46. 34%, P <0. 05). Conclusion Optimizing the nursing process of green channel is potentially effective in the shortening of time required for intravenous thrombolysis in AIS patients. (目的 探讨优化绿色通道护理流程对急性缺血性脑卒中(AIS)患者静脉溶栓时间节点的影响。方法 选取2020年11月—2021年10月急诊科接受静脉溶栓治疗的AIS患者99例为研究对象, 其中2020年11月—2021年3月流程优化前收治的41例为对照组, 2021年4月—10月流程优化后收治的48例作为观察组。比较两组患者入院至完成CT扫描时间、入院至签署知情同意书时间、入院至溶栓治疗开始时间(DNT)、和DNT≤60 min的患者占比。结果 观察组患者从进入急诊到完成 CT 扫描平均时间、书面签字同意溶栓治疗平均时长和DNT平均时长均较对照组缩短, 差异有统计学意义(P＜0. 05)。对照组19(46. 34%)例患者DNT≤35 min, 观察组43(89. 58%)例患者DNT≤35 min, 两组差异有统计学意义(P <0. 05)。结论 优化绿色通道护理流程能缩短AIS患者静脉溶栓相关节点所需时间。)